Expresión oral en el proceso de aprendizaje de Lengua y Literatura de los estudiantes de Segundo de Básica. - Quinga Gualotuña, Evelin Rosalva (2022)
The research starts from the following problem: How to improve oral expression in the process? learning of Language and Literature of the students of the second year of Basic General Education of the Fiscal Educational Unit "Nueva Aurora"? And it is proposed as a general objective: To evaluate the oral expression in the learning process of Language and Literature of the students of the second year of basic…” From a qualitative approach and an applied research, the Inductive method and the techniques of direct observation are assumed, the survey and interview, in addition, the criteria of specialists and users were used for the validation of the manual of verbal games; arriving at the following conclusions: the background, epistemological foundations and state of the art of learning language and literature and oral expression in students were determined, which served as a guideline to justify and design the proposal of the manual of verbal games, it was diagnosed the oral expression in the students of Basic General Education, which reveals a state of insufficiency that allowed justifying the proposal, the proposal was designed to contribute to the improvement of the problems of oral expression, which was validated through specialist criteria and users, demonstrating the viability and feasibility and the partial application of the manual of verbal games. This manual demonstrated its effectiveness in practice, since significant results are achieved in oral expression in most students.